Development of a progressive shelter system for post-disaster deployment in the Philippines - Mojica, Jaztin Adrian R.; Quiaoit, Daniel Mark D.
Disaster preparedness means establishing and strengthening capacities of communities to anticipate, cope, and recover from disasters. In the aftermath of a disaster, displaced families who could no longer return to their old homes may opt to settle on land provided by the government. The lands provided are assumed suitable for relocation and permanent use. However, it is important to provide a shelter that is easy and quick to deploy, but is already a part of a permanent structure. With this in mind, the study aims to produce a safe, economical, and serviceable progressive shelter system, that complies with internationally accepted guidelines and standards, as well as local building codes. Thus, the conceptualization of a cost-effective progressive shelter system for the Philippine setting that can be installed in a short amount of time and be upgraded to a permanent shelter is proposed. This study includes the design criteria for the progressive shelter system, the layout and schematic design of the shelter, and the materials to be used for the shelter in compliance with the created design criteria, and a construction and upgrade scheme that will transition the shelter into a permanent house.